Disappearance and survival of fermented beverages in the biosphere reserve Tehuacán-Cuicatlán, Mexico: The cases of Tolonche and Lapo - Ojeda-Linares, César Iván; Vallejo, Mariana; Casas, Alejandro (Frontiers in Sustainable Food Systems, 2023)
Traditional fermented products are disappearing from the local foodscapes due to social pressures and ecological changes that affect their production; it is therefore crucial to document local knowledge, which is crucial to maintain and recover local biocultural heritage and to contribute to food security. This study aims to document and foster the production of local traditional beverages by registering recipes of fermented beverages in the Tehuacán-Cuicatlán biosphere reserve in central Mexico, a region recognized for its great biocultural diversity. We identified five main fermented beverages in the research area, the most common beverages are those produced by agave species which include, mescal, pulque and an almost extinct beverage known as lapo which involves sugar cane as main substrate. We also identified a fermented beverage produced with several cacti fruits known as nochoctli and a traditional a fermented beverage produced with fruits of Schinus molle known as tolonche. We highlight the production of lapo and tolonche since these involved the incorporation of foreign substrates into the region after the Spaniard conquest and to their restricted distribution and almost extinction. The beverages tolonche and lapo are nowadays almost lost and only a few producers still prepare them to follow modified versions of the original recipe. This study included ethnographic research and participatory methods to engage residents in different steps of the production process. Lapo and tolonche were once important in the research area but almost became extinct until local people started to recently recover them. Traditional fermented beverages in Mexico play an important role in cultural identity and contribute to the local diet; nevertheless, several fermented beverages have not been recorded and have even become extinct. This work is an effort to promote and conserve traditional fermented beverages as valuable biocultural heritage by empowering people to make decisions about the use of locally available resources, which is crucial in times when food systems are highly vulnerable.